Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s42003-023-04689-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA origami presenting the receptor binding domain of SARS-CoV-2 elicit robust protective immune response

Abstract: Effective and safe vaccines are invaluable tools in the arsenal to fight infectious diseases. The rapid spreading of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) responsible for the coronavirus disease 2019 pandemic has highlighted the need to develop methods for rapid and efficient vaccine development. DNA origami nanoparticles (DNA-NPs) presenting multiple antigens in prescribed nanoscale patterns have recently emerged as a safe, efficient, and easily scalable alternative for rational design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Here, we designed the binding sequence to be complementary to a peptide nucleic acid (PNA) strand as this method allows the use of a shorter linker due to the higher affinity of PNA for DNA rather than DNA itself. We chose a recombinant protein G (PG) commonly used to bind and immobilize antibodies via their Fc domains . The PG has a free cysteine at its N-terminal that we used to conjugate with a PNA maleimide to form protein G-PNA (PG-PNA) as recently described .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we designed the binding sequence to be complementary to a peptide nucleic acid (PNA) strand as this method allows the use of a shorter linker due to the higher affinity of PNA for DNA rather than DNA itself. We chose a recombinant protein G (PG) commonly used to bind and immobilize antibodies via their Fc domains . The PG has a free cysteine at its N-terminal that we used to conjugate with a PNA maleimide to form protein G-PNA (PG-PNA) as recently described .…”
Section: Resultsmentioning
confidence: 99%
“…The unmodified PB DNA-NPs and PB DNA-NPs containing scaffolds that were produced using 10, 20, and 35% phosphorothioate-modified linkage (henceforth referred to as “αThiol”) as well as the multifunctional PB (multi-V: 7.5% biotin, 15% NH2, 15% αThiol) were assembled in the presence of either only FAM (5′-donor)-modified staple strands or staple strands having both FAM and TAMRA (5′-acceptor) together (Table S4). FAM and TAMRA staple strands have been positioned to ensure a distance of approximately 3 nm between the donor and acceptor to maximize FRET efficiency as previously used . Following purification using 100 kDa Amicon columns as described in Section , fluorescently labeled DNA-NPs were incubated in PBS that had been complemented with 20% mouse serum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, unlike protein scaffolds (virus-like particles, VLPs), the DNA-based scaffolds themselves, as thymus-independent antigens, induce only extrafollicular B-cell responses, thus avoiding scaffold-directed immunological memory that results in antibody dependent clearance of the vaccine platform. Almost at the same time, Oktay et al also demonstrated that precisely patterning ten copies of a reconstituted trimer of the RBD of SARS-CoV-2 along with CpG adjuvants on DNA origami was able to elicit a robust protective immunity against SARS-CoV-2 in mice . These works illustrated the potential of DNA nanotechnology for the construction of novel and highly effective subunit vaccines.…”
Section: Regulating Immunoreceptor Signaling With Functional Dnamentioning
confidence: 93%